Blockchain and Supply Chain Efficiency: Implications for Managerial Economics - Putri, Mardifa Wahyu; Chandini, Anggella; Putri, Finola Fiftem Eka; Andriadi, Jefri; Zefriyenni, Zefriyenni (Amkop Management Accounting Review (AMAR), 2025)
This study aims to examine the relationship between blockchain technology, supply chain efficiency, and its implications for decision making within the framework of managerial economics. Through a literature study approach, this study reviews and synthesizes various related literature to map the conceptual contribution of blockchain integration in supply chain management. The study's results demonstrate that the characteristics of blockchain, namely decentralization, immutability, and transparency, have a significant impact on operational efficiency, transaction cost reduction, increased supply chain visibility, and risk management. From a managerial economics perspective, blockchain implementation enables more rational and efficient decision-making through reducing information asymmetry, optimizing resource allocation, and transforming market structures within the supply chain ecosystem. However, the adoption of this technology also presents several challenges, including high implementation costs, the need for standardization, and adjustments to organizational structures. This study provides a conceptual foundation for managers and policymakers to understand how blockchain can be a strategic tool for improving corporate competitiveness through supply chain transformation.